Taxation of Income from Domestic and Cross-border Collective Investment A Qualitative and Quantitative Comparison - Oestreicher, Andreas; Hammer, Markus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The Fund Reporting Cloud® has made tax reporting less complex, but comparing the effective tax treatment of investment funds and their investors in an international environment is still an ambitious task. Against this background, this study examines the tax consequences at fund, asset, and investor level. In geographical terms our comparison covers eleven European countries, the USA, and Japan. Our analysis of the relevant tax provisions, which is of a primarily qualitative nature, is complemented by a quantitative comparison of the tax burden for a model investor investing assets nationally in the form of a collective investment. It will be of interest both for investors seeking tax advantages and for governments to check whether there is a need for tax reforms. It also ties in perfectly with the current evaluations at OECD level in the context of TRACE.
Introduction -- Analysis -- Country summaries.
Keywords: Law; Public finance; Law; International Economic Law, Trade Law; Business Taxation/Tax Law; Private International Law, International & Foreign Law, Comparative Law; Financial Law/Fiscal Law